COMPARING THE SUBGINGIGVAL MICROBIOME COMPOSITION DURING OXALIPLATIN CHEMOTHERAPY IN A PATIENT WITH COLON CANCER. CASE REPORT - Diana-Cristala Kapp; Sorina Mihaela Solomon; Cornelia Teodorescu; Ioana Sioustis; Liliana Păsărin; Silvia Mârţu (Romanian Dental Association for Education, 2019)
There is an uprising interest in the complex mechanisms of the subgingival microbiome and its interaction with the host immunity and tissues. Chemotherapy patients constitut a particular interest regarding the modifications of the subgingival microbiome given the secondary effects of the chemotherapy agents. Case presentation: a 67 year old male suffering of colon cancer was to start treatment with oxaliplatin. Materials and methods: Alongside the oncological examination, the patient was clinically examined and crevicular fluid samples were gathered before and after the first session of chemotherapy. The clinical examination consisted of Silness & Loe plaque and calculus index, probing depth (PD) and total attachment loss (TAL). The samples were then analysed using the Illumina 16s metagenomic kit (MiSeq platform) and the results were aligned with international databases. Ribosomal RNA gene sequences were amplified using broad-range bacterial primers, cloned and sequenced. Results: There are several modifications at each bacterial level of classification. Most are consistent with current scientific studies. The clinical modifications were important especially at PD and TAL where the loss was 3 mm in PD and 6.33 mm in TAL. Conclusion: Chemotherapy with oxaliplatin may induce modifications in the subgingival microbiome that, in turn, can lead to the progression of periodontal disease in oncological patients. Further studies are necessary to help understand the complex mechanations of the subgingival microbiome, hemotherapy and their relation.